Amide derivatives of 4-azaindole: Design, synthesis, and EGFR targeting anticancer agents. Issue 1 (2nd January 2020) - Venkat Swamy, Puli; Kiran Kumar, Vukoti; Radhakrishnam Raju, Ruddarraju; Venkata Reddy, Regalla; Chatterjee, Anindita; Kiran, Gangarapu; Sridhar, Gattu
Abstract: A series of amide derivatives of azaindole-oxazoles (11a-n ) were designed and synthesized and their structures were confirmed by 1 HNMR, 13 CNMR and mass spectral analysis. Further, these derivatives were screened for their anticancer activity against human cancer cell lines viz; MCF7 (breast), A549 (lung) and A375 (melanoma). In vitro anticancer activity screening indicated that most of the hybrids exhibited potent inhibitory activities in a variety of cancer cell lines. Among the compounds 11d, 11e, 11f, 11j, 11k, 11l, 11m, and 11n were exhibited more potent activity than standard, in those mainly two compounds 11m and 11j were exhibited excellent activity in MCF-7 cell line with IC50 values 0.034 and 0.036 µM. Moreover, all these compounds were carried out their molecular docking studies on EGFR receptor results indicated that two potent compounds 11m and 11j were strongly binds to protein EGFR (PDB ID: 4hjo). It was found that the energy calculations were in good agreement with the observed IC50 values. GRAPHICAL ABSTRACT: